2020
DOI: 10.1136/bmjnph-2020-000091
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to dietary and physical activity guidelines among shift workers: associations with individual and work-related factors

Abstract: ObjectivesShift work is associated with adverse effects on the health and lifestyle behaviours of employees. This study aimed to examine factors associated with adherence among shift workers to selected indicators of dietary and physical activity guidelines.MethodsA cross-sectional study was conducted on 1300 shift workers. Data were collected using a 15 minute telephone-administered questionnaire. Logistic regression methods were used for data analysis.ResultsMale shift workers (p<0.001, OR=0.55, 95% CI 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Accumulated evidence from previous studies has shown a decrease in medication adherence and QOL, such as sleep disorders, in shift workers [ 31 32 ]. In addition, physical laborers were associated with an increased risk of poor adherence compared with other types of workers [ 31 33 ]. Our data highlight the need for strategies to improve non-adherence in patients with occupations, particularly those who work manually or are shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence from previous studies has shown a decrease in medication adherence and QOL, such as sleep disorders, in shift workers [ 31 32 ]. In addition, physical laborers were associated with an increased risk of poor adherence compared with other types of workers [ 31 33 ]. Our data highlight the need for strategies to improve non-adherence in patients with occupations, particularly those who work manually or are shift workers.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the food consumption of populations is a complex task, and in shift workers, there are signi cant additional methodological challenges. Variability in work patterns and the availability of food during the night can in uence both the calorie intake and the variety of food items consumed (Kelly et al, 2023;Souza et al, 2019). In addition, the lack of adequate facilities for eating at night can make it di cult to adopt healthy eating patterns (Reeves et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The workplace is complex, with multiple factors and determinants that influence physical activity [ 18 , 19 ]. For shift workers, lack of time and work-related fatigue may explain workers’ low levels of physical activity [ 20 ]. According to a study conducted in shift working South African doctors, more steps were reported when working longer shifts, thus resulting in more physical activity at work [ 21 ].…”
Section: Introductionmentioning
confidence: 99%